Allopregnanolone enhances the neurogenesis of midbrain dopaminergic neurons in APPswe/PSEN1 mice. (2nd April 2015) - Zhang, P.; Xie, M.Q.; Ding, Y-Q.; Liao, M.; Qi, S.S.; Chen, S.X.; Gu, Q.Q.; Zhou, P.; Sun, C.Y.
Highlights: Evaluate the efficacy of APα in neurogenesis of midbrain dopaminergic neurons. Measure APα concentration and the numbers of positive neurons. Decreasing of TH neurons was present prior to Aβ plaques in 2xTgAD mice. APα treatment prevented the decrease of TH neurons by increasing TH/BrdU neurons. APα delayed neurogenic deficits in SNpc of AD mice by promoting neurogenesis. Abstract: An earlier study has demonstrated that exogenous allopregnanolone (APα) can reverse the reduction of tyrosine hydroxylase (TH)-positive neurons in the substantia nigra pars compacta (SNpc) of 3-month-old male triple transgenic Alzheimer's disease mouse (3xTgAD). This paper is focused on further clarifying the origin of these new-born TH-positive neurons induced by exogenous APα treatment. We performed a deeper research in another AD mouse model, 4-month-old male APPswe/PSEN1 double transgenic AD mouse (2xTgAD) by measuring APα concentration and counting immunopositive neurons using enzyme-linked immunosorbent assay (ELISA) and unbiased stereology. It was found that endogenous APα level and the number of TH-positive neurons were reduced in the 2xTgAD mice, and these reductions were present prior to the appearance of β-amyloid (Aβ)-positive plaques. Furthermore, a single 20 mg/kg of exogenous APα treatment prevented the decline of total neurons, TH-positive neurons and TH/bromodeoxyuridine (BrdU) double-positive neurons in the SNpc of 2xTgAD mice although the decreased intensity of TH-positive fibers was not rescued in the striatum. It was also noted that exogenous APα administration had an apparent increase in the doublecortin (DCX)-positive neurons and DCX/BrdU double-positive neurons of subventricular zone (SVZ), as well as in the percentage of neuronal nuclear antigen (NeuN)/BrdU double-positive neurons of the SNpc in the 2xTgAD mice. These findings indicate that a lower level of endogenous APα is implicated in the loss of midbrain dopaminergic neurons in the 2xTgAD mice, and exogenous APα-induced a significant increase in the new-born dopaminergic neurons might be derived from the proliferating and differentiation of neural stem niche of SVZ.